Rancang Bangun Aplikasi Penjualan dan Tracking Progress Produksi Percetakan Berbasis Web pada CV Abadi - Ghea Cikita Karina; M. J. Dewiyani Sunarto; Agus Dwi Churniawan (Jurnal Sistem Informasi Universitas Dinamika, 2022)
One of the service companies which specializes in printing is CV Abadi. The products produced by CV Abadi include invitations, books, brochures, and magazines. The business process in CV Abadi starts when the customer asks for the unit price of the product to be ordered, then the customer provides the product design to the sales department. Furthermore, the sales department will make a proof of order to the customer. The production department will prepare raw materials and carry out the production process based on the proof of order. After the product is produced according to the order, the sales department will inform the customer. Then the customer makes payment to the sales department. The problem is that the customer has to wait a long time to ensure the price of the product ordered, the sales department does not know the due date of the customer's order due to manual checking, and if the customer wants to know how far the production process of the ordered product (tracking the production progress) is, the customer must ask to the sales department. To overcome the problems above, the solution given is to design a sales application and track the progress of web-based printing production at CV Abadi. This application has several features such as calculating the selling price of products, managing customer orders, being able to view the status of customer payments, being able to track the progress of production status with notifications via email, and displaying up-to-date product orders sales information. Based on the results of trials with black boxes, it is found that all functions in the application can work well and solve existing problems. The application will display an automatic product price list according to the product name and calculate the payment price when inputting the number of products to be ordered. The sales department can find out the due date and see the tracking of the production progress of customer orders on the schedule page. During the process of marketing and tracking progress, the printing production that is conducted by CV Abadi, there are some problems, such as the customer asks about the price of the product unit which he/she is going to order but he/she usually must wait long enough, the marketing division doesn’t know the dates of the due date of the customer’s order, the searching of data still done manually so it makes the customer’s order pass the due date of finishing of the order, the marketing division doesn’t know the due date of the customer’s payment which still has some debts, the searching of the data is still done manually so it takes a long time so there are some customers who have passed their due dates of payments, the customer asks if the company has or has not finished the product he/she ordered but the marketing division must check it out or directly ask the production division, (when) the owner wants to know the income that the company gets during a certain period, the marketing division still do the information presentation manually so it takes a long time to show the information that the owner asks. To overcome the problems above, the solution given is the use of marketing applications and tracking the progress of the printing production which is based on the web in CV Abadi. The application has some features, such as counting the selling price of the product, managing the orders of the customers, and the payments from the customers. The application of marketing and tracking progress of the printing production which is based on the web in CV Abadi produces the reports needed by the owner where the application can provide the information about the progress of the customer’s orders, and the status of the payments.